2020
DOI: 10.3390/plants9111458
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Native Plants Growing on a Pb/Zn Mining Area in Eastern Morocco: Perspectives for Phytoremediation

Abstract: Screening of native plant species from mining sites can lead to identify suitable plants for phytoremediation approaches. In this study, we assayed heavy metals tolerance and accumulation in native and dominant plants growing on abandoned Pb/Zn mining site in eastern Morocco. Soil samples and native plants were collected and analyzed for As, Cd, Cu, Ni, Sb, Pb, and Zn concentrations. Bioconcentration factor (BCF), translocation factor (TF), and biological accumulation coefficient (BAC) were determined for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 76 publications
5
37
6
Order By: Relevance
“…The soil-to-plant transfer coefficient (TC) is a useful index showing the mobility of the studied PTEs to be absorbed by a test plant/crop. Hasnaoui et al [46] measured PTE concentrations in native plants grown in a mining area, and reported a TC for Zn (in aerial tissues) equal to 190 (per mille), lower than our Zn TC values reported for Eretria (260) and Domokos (470). In the same industrial area of Volos as studied here, Antoniadis et al [21] measured the TC values of maize and found that Mn in maize shoots were higher than the value in our work (95.3 vs. 52.1) and the Mn TC in grains lower than that in our work (6.58 vs. 47.5).…”
Section: Discussioncontrasting
confidence: 82%
“…The soil-to-plant transfer coefficient (TC) is a useful index showing the mobility of the studied PTEs to be absorbed by a test plant/crop. Hasnaoui et al [46] measured PTE concentrations in native plants grown in a mining area, and reported a TC for Zn (in aerial tissues) equal to 190 (per mille), lower than our Zn TC values reported for Eretria (260) and Domokos (470). In the same industrial area of Volos as studied here, Antoniadis et al [21] measured the TC values of maize and found that Mn in maize shoots were higher than the value in our work (95.3 vs. 52.1) and the Mn TC in grains lower than that in our work (6.58 vs. 47.5).…”
Section: Discussioncontrasting
confidence: 82%
“…In order to achieve this purpose, it is necessary to select the best performing plant species with a special focus on native taxa. Owing this issue, several reasons promote the implementation of autochthonous plants over non-native species: (i) they are adapted to local climate/adverse conditions (Pandey and Singh 2012 ; El Hasnaoui et al 2020 ) and are stronger in terms of growth, survival, and reproduction under environmental stress (Midhat et al 2017 ); (ii) their use can preserve the plant diversity of the natural territories (Cao et al 2009 ; Bacchetta et al 2012 , 2015 ; Concas et al 2015a ); (iii) they help to start the rehabilitation of vegetational dynamics by the improvement of the physical-chemical properties of the substrates (Vacca 2000 ; Vacca et al 2017 ), and (iv) they help to the establishment of a long-term plant canopy on mine wastes with a relatively low cost inputs and limited maintenance (Bacchetta et al 2007a ; Pandey et al 2015 ; Monaci et al 2020 ; Zine et al 2020 ). All these points are pieces of a more holistic and sustainable approach in phytoremediation (Pandey et al 2015 ; Pandey and Omesh Bajpai 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mining and metallurgy of Zn-Pb ores in the 19th and 20th centuries has had a major impact on the natural environment in Europe. On sites where zinc, lead, copper, tin, and other metal ores are mined and processed, the most significant environmental problem is potentially toxic metals contamination of soil and water and their transfer to biotic environments [ 1 , 2 , 3 ]. Mining and the associated post-mining landscape constitute an ecological niche [ 4 , 5 ], where a particular succession of vegetation develops on Zn-, Pb-, Cd-, As-, and Fe-rich soils [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mining and the associated post-mining landscape constitute an ecological niche [ 4 , 5 ], where a particular succession of vegetation develops on Zn-, Pb-, Cd-, As-, and Fe-rich soils [ 6 ]. Botanical and pedological studies in areas affected by Zn-Pb-Fe ore mining have been conducted in Belgium [ 7 ], Germany [ 8 ], Spain [ 9 ], Slovenia [ 10 , 11 ], China [ 12 , 13 , 14 ], Morocco [ 3 , 15 ], and southern Poland [ 6 ].…”
Section: Introductionmentioning
confidence: 99%